Simulation of Flow Regime of Dibdibba Dandy Aquifer inSafwan-Zubair Area, South of Iraq - Atiaa, Alaa; Al-Aboodi , Ali (Iraqi Journal of Science, 2025)
A two-dimensional model is constructed to simulate the flow regime of theupper part of Dibdibba sandy aquifer in Safwan-Zubair area, south of Iraq. Althoughthe Dibdibba Formation is a multi-layer system in the surveyed area, the suggestedconceptual model which is advocated to simulate the flow regime of aquifer is fixedfor one layer, i.e., the activity of the deeper aquifer is negligible. The model iscalibrated using trial and error procedure in two stages: steady state followed bytransient state. The outcome of the calibration process demonstrated considerablespatial variations in transmissivities and storativites of the aquifer system. A verygood similarity between the observed and simulated groundwater levels in the steadystate calibration is observed. A reasonable representation of the hydraulic gradientover the mode area which consistent with relative magnitude of hydraulicconductivies is obtained during this calibration stage. Transient calibration isundertaken to calibrate the aquifer storage parameter after the steady state calibrationis achieved. The transient calibration results are evaluated by comparing water levelsat eight observation wells. Good matches are observed for all cases. The reliabilitiesof calibrated parameters are checked through sensitivity analysis. Verification test isalso added to ensure that the calibrated model could be an adequate counterpart ofthe actual groundwater system and to verify the reliability of the model results. Themodel is verified against the measured heads during June 2000. The verified modelis utilized to predict behaviour of the aquifer over a planning horizon of 10 years(2000-2010) under two developments scenarios. The management plans areundertaken with continuity of existing trend of growth of pumping wells, i.e., 200wells per year and without growth and still the situation is similar to that in year2000. The first run indicates that the decline of groundwater heads of about onemeter in the central part of the area and of about 0.5 meter in the northern andwestern parts is expected. The outcome of the second run demonstrates that nosignificant changes from 2000 status have occured. The calibrated model can beused, if necessary data is available, to establish the responses of the aquifer toartificial recharge which is suggested to enhance the water availability and rebalancethe aquifer in other context.